(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: To analyze the incidence and risk factors for development hernia after elective lower midline caesarean section(ElMCS). Method: A prospective cohort study of 284 women for development of incisional hernia after repeated elective midline CS. Patients enrollment done from April 13th 2001 and December 12th 2002. follow up to two years for hernia development. Hernias were identified radiographically or during physical exam. 2-year hernia rates were calculated. Patients were distributed in two groups, study group consisted of women who had incisional hernia and control group consisted from women who had not within 2-years postoperatively. Within the two groups potential risk factors (age, body mass index (BMI), parity, number of previous cesareans, chronic cough, diabetes mellitus(DM), heart disease, low serum albumin, type of previous incision, anesthesia type, presence of postoperative fever and wound complications) were collected and statistically analyzed with the development of incisional hernia (IH). Setting: Prince Hashem Ben Al-Hussein Hospital, Jordanian Royal Medical Services of Jordan / Zarqa. Results: The 2-year hernia was 5.6 % .Independent risk factors of IH development include: increase in number of previous CSs, wound complications and obesity. Conclusion: An incisional hernia is higher than previously estimated in women undergoing ElMCS. Counseling on the family size will reduce the chance for further CS with its associated risk. Also measures to reduce wound infection after surgery may reduce the incidence of incisional hernia following ElMCS. DOI: http://dx.doi.org/10.3329/bjog.v25i1.13724 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(1) : 9-14